Catastrophic antiphospholipid syndrome: current aspects of pathogenesis, diagnosis and treatment - A. A. Klimenko; A. S. Gaffarova; N. A. Demidova (Современная ревматология)
Catastrophic antiphospholipid syndrome (CAPS) is a life-threatening condition associated with the development of thrombotic occlusion of microvasculature vessels, with a mortality rate of about 50%.The pathogenesis of CAPS is based on cellular activation, complement system induction, cytokine stimulation, inhibition of anticoagulant factors and fibrinolysis, which leads to progressive thrombotic microangiopathy, disseminated intravascular coagulation (DIC), and systemic inflammatory response syndrome. Classification criteria for CAPS include microthrombotic involvement of ≥3 organs (most commonly lungs, kidneys, and central nervous system) for ≤1 week with high titers of antiphospholipid antibodies.Differential diagnosis is carried out with DIC, heparin-induced thrombocytopenia, hemolytic uremic syndrome, HELLP syndrome, sepsis. Treatment of CAPS in the acute phase involves anticoagulant and immunosuppressive therapy (glucocorticoids, plasmapheresis, IV immunoglobulin, rituximab, eculizumab). Timely diagnosis and adequately selected treatment of CAPS can reduce mortality from 50 to 30%.Further study of CAPS is needed to improve the prognosis and increase the life expectancy of patients.